The Making of a Culture Hero: Jurgis Eišiškietis of Many Hats and his Milieu in Sources and Historiography - Ališauskas, Vytautas (Senoji Lietuvos literatūra, 2024)
The study focuses on the identity of Jurgis Eišiškietis (Georgius de Eyxyski; Georg Eyschitzki), a Master of Liberal Arts, and on his role in the efforts to open a secular private school for the sons of the nobility in Vilnius. Two sources related to him are extant: (1) an entry in the protocols of the capitular session of the Vilnius Cathedral Chapter of 28 April 1539 and (2) a letter of Duke Albert of Prussia (Albrecht von Preußen) to Philipp Melanchthon of 16 June 1541, recommending Jurgis of Eišiškės, who is going to the University of Wittenberg, to his care.The study states that the main initiator of the school was Albertas Goštautas, the grand chancellor of the Grand Duchy of Lithuania. It is quite safe to say that Goštautas’s project of the reform of the state of Lithuania included the necessity to create educational institutions that would nurture the political class. It is quite likely that Goštautas’s secretary Jan Wilamowski was his de facto trustee for education. As a clergyman of the lower orders and a Master of Liberal Arts, Jurgis Eišiškietis fulfilled the qualifications of a rector of a cathedral school. After the death of his patron Albertas Goštautas (late in 1539) and with the support of Duke Albert of Prussia, Jurgis was probably looking for new prospects and was recommended by him for studies at the prestigious University of Wittenberg. It cannot lead to the conclusion that Jurgis had broken with his former denomination and become a Protestant, and all the more reason not to assume that the initiative to establish the school was related to the desire to spread Protestant ideas in Vilnius.A critical review of Lithuanian and Polish historiography aims at refuting and rejecting the errors and hypotheses that have accumulated over time and are no longer relevant. Identification of Jurgis Eišiškietis with Jurgis Zablockis, an early Protestant author and a preceptor of young people, as well as with Gregorius Vilnensis, the pastor of Rusnė, is rejected. There are no direct confirmations that Jurgis of Eišiškės was the same person as Georgius Haustintz Lituanus / Georgius Hauschicz Lituanus / Magister Georgius Heuschitz, Lituanus, a student of Wittenberg and Königsberg universities. No scholar has been able to find out what Haustintz etc. means, so the firm identification of this student with Jurgis of Eišišiškės, which has taken root in German studies and has been adopted from them in Lithuania, cannot be considered justified.The workings of historical imagination itself are equally interesting and worthy of further exploration. Historians of Protestantism in Lithuania have created various stories about Jurgis Eišiškietis’s alleged connections with the figures of early Protestantism, especially Abraham Kulvietis, and about his later life. These stories are not based on any sources. In our study, the figure of Jurgis Eišiškietis and the situations linked to previous research on him are described by the metaphors of ‘the grotesque’ and ‘le théâtre d’ombres chinoises’. They point to the inconstancy and incompleteness of the images and at the same time to their subordination to the historian’s individual imagination and taste.
Keywords: Jurgis Eišiškietis; Albertas Goštautas; Georgius Haustintz Lituanus; Reformation; Vilnius Cathedral school